İş Sözleşmesinin Bulaşıcı Hastalık Nedeniyle İşçi Tarafından Haklı Feshi - (:unkn) unknown (My University, 2020)
İş Kanunu’nun m.24/I-(b) bendine göre, işçinin haklı sebeple derhal fesih hakkına sahip olabilmesi için, kendisinin değil sık sık buluşup görüştüğü “işveren” veya “başka bir işçinin” bulaşıcı veya işi ile bağdaşmayan bir hastalığa yakalanması gerekir. Nezle ve grip gibi hayati tehlikesi olmayan bulaşıcı hastalıklar, işçiye haklı sebeple fesih hakkı vermez. Bu bağlamda, işveren, işyerinde yeni tip korona (Covid-19) hastalığına karşı her türlü önlemi almışsa işçinin sürekli olarak yakından ve doğrudan buluşup görüştüğü işveren yahut başka bir işçinin korona hastalığına yakalanması ve karantinaya alınıp tedavilerine başlanmış olmaları halinde işçi iş sözleşmesini haklı nedene dayalı olarak feshedemeyecektir.

According to Article 24 / I- (b) of the La?bor Code, in order for the worker to have the right to terminate immediately with a just cause, not her or himself but the “employ?er” or “another worker” with whom he or she meets frequently must have a contagious dis?ease or a disease which is incompatible with his or her job. Non-life-threatening infectious diseases such as cold and flu do not give the worker the right to terminate with just cause. In this context, if the employer has taken all kind of precautions against the new type of corona (Covid-19) disease at the workplace, the employee will not be able to terminate the employment contract based on just cause due to close and direct interaction with the infected if the quarantine and treatment processes have started.
Rightful Termination of The Labor Contract by The Worker Due to Contagious Disease